Življenje in delo Vide Taufer - Božič, Boštjan (Jezik in slovstvo, 2004)
The present article is a recollection of memories from the life and work of poet Vida Taufer (1903-1966), who in spite of promising reviews during her lifetime, has begun to fall into oblivion. In recent literary histories and surveys, Vida Taufer, who excelled in honest, genuinely felt harmonious lyricism radiating the faith and mentality of many a Slovene woman born duringthe first half of the 20th century, appears only sporadically, or is notconsidered at all.
Keywords: Taufer, Vida, 1903-1966; Slovene literature; slovenska književnost; slovenska poezija; slovenske pesnice; biografije; literarne študije